The Clinical Course and Prognostic Problems of Youth Depressions with Attenuated Schizophrenic Symptoms - V. G. Kaleda; M. A. Omelchenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
Objective Clinical and follow-up verification of Attenuated Schizophrenic Symptoms (ASS) in the first youth depressive episode as early markers of the schizophrenic process, establishing further variants of the course of the disorder and its outcomes.Materials and methods. 124 young inpatients (averaged age 19,6±2,3 years) with the first depressive episode with ASS were examined. The control group consisted of 27 patients with youth depression without ASS. All patients have been tracked for at least five years. The average follow-up period was 7,1±1,6 years. The HDRS, SOPS, SANS and PSP scales were used to assess the symptomatic and functional outcomes. Statistical analysis was carried out using STATISTICA 12.Results. The typological classification of youth depressions (ASD) with ASS has been developed with the identification of three main types: (1) with attenuated positive symptoms (APS), (2) with attenuated negative symptoms (ANS), and (3) with attenuated symptoms of disorganization. Youth depression with ASS, compared to the control group, is more likely to move into chronic forms, has reliably worse functional and symptomatic outcomes, and is more associated with the diagnosis of schizophrenic spectrum disorders at five years follow-up.Conclusion. Attenuated schizophrenic symptoms in the structure of youth depressions have high affinity to each other, indicating a common pathogenic mechanism of their formation, and also have predicate value as risk factors for schizophrenia.